Pressure and pressure derivative analysis for a well in a radial composite reservoir with a non-newtonian/newtonian interface - Escobar, Freddy-Humberto; Martínez, Javier-Andrés; Montealegre-Madero, Matilde (CT&F - Ciencia, Tecnología y Futuro, 2020)
In many activities of the oil industry, engineers have to deal with completion and stimulation treatment fluids such as polymer solutions and some heavy crude oils which obey a non-Newtonian power-law behavior. When it is required to conduct a treatment with a non-Newtonian fluid in an oil-bearing formation, this comes in contact with conventional oil which possesses a Newtonian nature. This implies the definition of two media with entirely different mobilities. If a pressure test is run in such a system, the interpretation of data from such a test through the use of conventional straight-line method may be erroneous and may not provide a way for verification of the results obtained. In this work, the signature of the pressure derivative curve is investigated to understand and ease the interpretation of the well test data in reservoirs with non-Newtonian power-law fluids. Specifically, the Tiab’s Direct Synthesis (TDS) technique is implemented using some characteristics features found on the pressure and pressure derivative curves. Hence, new equations are introduced to estimate permeability, non-Newtonian bank radius and skin factor. Permeability can be verified. The proposed methodology was successfully verified by its application to an example reported in the literature and a synthetic case.